SIKAP RAMAJA TERHADAP KEGIATAN KEAGAMAAN DI RW 04 KELURAHAN TANGKERANG TIMUR KECAMATAN TENAYAN RAYA - Wan Putri Dahlia Dahlia Putri Dahlia; Aswandi Bahar Bahar; Said Suhil Achmad3 Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: this research caused by the negative attitude of teenagers in religious activity at RW 04 Kelurahan Tangkerang Timur Kecamatan Tenayan Raya. Formulation of the problem in this study is whether the attitude of teenagers have positive or negative action in religious activity at RW 04 Kelurahan Tangkerang Timur Kecamatan Tenayan Raya. The purpose of this study is to know  the attitude of teenagers at RW 04 Kelurahan Tangkerang Timur Kecamatan Tenayan Raya in religious activity have positive or negative action. The populations in this research are 287 teenagers and the samples of this research are 74 teenagers with critis level 10%, the sample used is proporsionate stratified random sampling. The instrument to collect the data is questionnaire containing 64 items and after to try out the valid statements become 62 items to use in research. Analize data used descriptive analize. From the answer percentase can calculated, have the result as cognitive indicator which the positive attitude of teenagers 89,24% and negative 2,25%. Between as affective aspect which the positive attitude of teenagers 44,21% dan negative 47,51%. Next, can to know from konative aspect which  the positive attitude of teenagers 43,67% dan negative 47,63%. Key words: attitude, the attitude of teenagers, religious activity